Variation of Type of Spleen of Bangladeshi Cadavar - Khan, Nilufar Jahan; Mannan, Sabina; Khalil, Mohsin; Sultana, Seheli Zannat; Sultana, Nahida; Sumi, Sharmin Akter; Akter, Sakera (Bangladesh Journal of Anatomy, 2017)
Context: Spleen is a haemo-lymph organ and belongs to the reticuloendothelial system of human body developed from mesodermal proliferation between the two leaves of dorsal mesogastrium. It consists of a large encapsulated mass comprising of lymphoid and vascular tissues. Spleen is highly vascular, friable and elastic. It is purple in colour and moves with respiration. The spleen plays a central role in the pathophysiology of several potentially severe diseases such as inherited red cell membrane disorders, hemolytic anaemias and malaria. Study was done whether the specimens can be grouped into various types based on their morphology and the length of the hilum. Materials and Methods: A cross sectional descriptive study was carried out in the Department of Anatomy, Mymensingh Medical College on 65 postmortem human Spleen (34 of male and 31 of female) to find out the different types of spleen of Bangladeshi people by purposive sampling technique. Dissection was performed according to standard autopsy techniques. For statistical analysis, unpaired student‘t’ test was used. Result:There were three types of spleen, among them, 34(52.30%)specimens were distributed in type,16(23.07%)specimens were intermediate in type and15 (24.61%) specimens were compact in type. Conclusion : The sixty five postmortem human spleen could be classified into three morphological types, distributed, compact and intermediate type, and this grouping seems valid, according to its external features and length of the hilum. Bangladesh Journal of Anatomy July 2017, Vol. 15, No. 2 , pp. 45-47